Desenvolvimento e caracterização de matriz porosa de quitosana incorporadas com rutina - Arruda, Iza Natália Queiroz de (2015)
Porous scaffold development is of major interest to the food industry due to their ability to release coumpounds through an intelligent system of interlinked cavities, which aims to extend the shelf-life of food products by stabilizing bioactive components. Due to the high increase in biomaterials studies, chitosan is presented as a potential biomaterial, having peculiar features such as biocompatibility, non-toxicity, bactericidal action, besides being a non-reactive polymer, allowing the combination with other compounds. Chitosan features facilitate the controlled release process of flavonoids, which are natural pigments found in plants, with protective action in the body, against free radicals. As a result, this study developed porous scaffold of chitosan with entrapped Rutin, in order to act in foods with antioxidants controlled release. Chitosan/flavonoids scaffolds were prepared by the method of the submission of a chitosan solution in NaOH alkaline solution. The scaffolds with flavonoids were characterized by FTIR techniques, TG-DSC, X-ray diffraction, SEM and controlled release assay. The results show the efficacy of the incorporation of flavonoids into the porous chitosan scaffold, since there ware changes in the infrared spectrum peaks. The DSC curve suggests a physical interaction between the polymer and flavonoids. The x-ray diffraction showed that the polymer matrix has a crystalline behavior, possibly characterized by the insertion of Rutin on the chitosan polymer chain. The SEM confirmed the porous scaffold formation, by analyzing the morphology of the material in which it was observed the formation of interconnected cavities. The controlled release of Rutin was satisfactory, since the scaffold showed a linear release and constant manner, making it a suitable material for rapid release systems. Finally, the porous scaffold exhibit features of a biomaterial with wide application in the food industry through the controlled release of the sipped flavonoids.